(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The legal determination of the responsibility of the maritime carrier was initiated to veduce the burden of liability for the carrier, but there are cases in which the carrier does not benefit from this determination, in the event that the shipper declares the nature and value of the goods in the cargo bond, as well as in the event that the carrier commits or refrains from doing so in order to damage the shipper or negligence accompanied by the realization that damage may occur. In the event that any of these cases are occurred, the carrier is deprived of the principle of determining liability and is obliged to compensate for the value of the goods as mentioned in the cargo bond or as specified by the shipper. This subject has been studied in the light of international agreements and Syrian law, through which I have addressed the issue of mentioning the purchase bill in the cargo bond, and we have concluded from this research that it is necessary to find rules that address the issue of the real value of goods and their value and adopt the modern concept of cheating.